2016
DOI: 10.1097/md.0000000000004821
|View full text |Cite
|
Sign up to set email alerts
|

The aspartate aminotransferase-to-alanine aminotransferase ratio predicts all-cause and cardiovascular mortality in patients with type 2 diabetes

Abstract: An increased aspartate aminotransferase-to-alanine aminotransferase ratio (AAR) has been widely used as a marker of advanced hepatic fibrosis. Increased AAR was also shown to be significantly associated with the risk of developing cardiovascular (CV) disease. The aim of this study was to assess the relationship between the AAR and mortality risk in a well-characterized cohort of patients with type 2 diabetes.A cohort of 2529 type 2 diabetic outpatients was followed-up for 6 years to collect cause-specific mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 36 publications
5
59
1
Order By: Relevance
“…Zoppini et al [27] studied patients with type 2 diabetes mellitus and found that the AST/ALT ratio positively correlated with CVD mortality; however, as in the above studies, they did not include HFrEF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zoppini et al [27] studied patients with type 2 diabetes mellitus and found that the AST/ALT ratio positively correlated with CVD mortality; however, as in the above studies, they did not include HFrEF patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Italy 6-year follow-up study with 2529 diabetes showed that the AST/ALT ratio had an independent association with all-cause and CVD mortality. Patients with a known history of drug-induced liver injury, viral hepatitis, cirrhosis of any etiology, and hemochromatosis were also excluded, but those with a history of CVD failed to be excluded in this study [25]. More recently, a 10year follow-up prospective study of 29,316 participants aged between 25 and 84 years from the United Kingdom showed that an increased AST/ALT ratio were at signi cant risk of developing CVD episodes in male participants but not those female, with no baseline pre-existing CVD [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous non-invasive methods that can be used for the prediction of fibrosis, including the AST/ALT ratio (AAR), APRI, FIB4 and the NAFLD fibrosis score [13,14,[16][17][18]. For the aim of the study, it was important that we choose a parameter that has been used in predicting cardiovascular diseases [19,[37][38][39][40][41]. Therefore, we used AAR for the prediction of fibrosis risk in CD patients.…”
Section: Discussionmentioning
confidence: 99%